Seedcorn maggot, Delia platura (Meigen) (Insecta: Diptera: Anthomyiidae) - Harsimran Kaur Gill; Gaurav Goyal; Jennifer L. Gillett-Kaufman (EDIS, 2013)
The seedcorn maggot is a polyphagous pest, affecting more than 40 different host plants. It is an important pest of germinating soybeans and corn, and also attacks a wide range of horticultural crops including beans, peas, cucumber, melon, onion, pepper, potato, and other vegetables. Seedcorn maggots damage newly planted seeds by feeding on seed contents, often leaving empty seed shells and preventing germination. Although usually no more than 2% of the seedlings get infested by this insect, 30% to 60% plant loss may occur in the field. This 5-page fact sheet was written by Harsimran Kaur Gill, Gaurav Goyal, and Jennifer L. Gillett-Kaufman, and published by the UF Department of Entomology and Nematology, July 2013.